2022
DOI: 10.3390/ijms23105824
|View full text |Cite
|
Sign up to set email alerts
|

Functional RNA Dynamics Are Progressively Governed by RNA Destabilization during the Adaptation to Chronic Hypoxia

Abstract: Previous studies towards reduced oxygen availability have mostly focused on changes in total mRNA expression, neglecting underlying transcriptional and post-transcriptional events. Therefore, we generated a comprehensive overview of hypoxia-induced changes in total mRNA expression, global de novo transcription, and mRNA stability in monocytic THP-1 cells. Since hypoxic episodes often persist for prolonged periods, we further compared the adaptation to acute and chronic hypoxia. While total mRNA changes correla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 48 publications
2
3
0
Order By: Relevance
“…Two other studies have observed widespread hypoxic mRNA decay in generic tissue culture models, supporting our findings in primary human macrophages 68, 69 . Using conventional mRNA lifetime calculations from actinomycinD transcription assays and a s 4 U pull-down approach in HUVECs, Tiana et al find that decay rates are about 1.6 times faster in hypoxia for a dataset of a few hundred genes 69 .…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Two other studies have observed widespread hypoxic mRNA decay in generic tissue culture models, supporting our findings in primary human macrophages 68, 69 . Using conventional mRNA lifetime calculations from actinomycinD transcription assays and a s 4 U pull-down approach in HUVECs, Tiana et al find that decay rates are about 1.6 times faster in hypoxia for a dataset of a few hundred genes 69 .…”
Section: Discussionsupporting
confidence: 91%
“…Our work suggests that either hypoxia alone does not induce these pathways in tumors, or that inflammatory activation is enough to drive gene expression of these factors in the opposite direction. Two other studies have observed widespread hypoxic mRNA decay in generic tissue culture models, supporting our findings in primary human macrophages 68,69 . Using conventional mRNA lifetime calculations from actinomycinD transcription assays and a s 4 U pull-down approach in HUVECs, Tiana et al find that decay rates are about 1.6 times faster in hypoxia for a dataset of a few hundred genes 69 .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Since hypoxia is a major contributing factor to various immune system-associated diseases, we determined RNA dynamics in human monocytic THP-1 cells in response to acute (8 h 1% O 2 = AH) and chronic (72 h 1% O 2 = CH) hypoxia ( 20 ). In line with the major regulatory impact of hypoxia, 2632 transcripts appeared differentially expressed ( padj < 0.05, |log2FC| > 0.3) between normoxia (21% O 2 = N) and hypoxia (AH and/or CH), however, following different regulatory dynamics ( Figure 1A ).…”
Section: Resultsmentioning
confidence: 99%
“…Previously, we characterized transcriptome-wide changes in de novo synthesis and RNA stability under hypoxia in monocytes by a metabolic labeling approach. Here, we focused on total mRNA changes within the previously published comprehensive metabolic RNA sequencing data of THP-1 cells incubated for 8 h and for 72 h under hypoxia (acute hypoxia (= AH) and chronic hypoxia (= CH), respectively), or under normoxia (N) (GSM5994456 to GSM5994464) ( 20 ). For differential gene expression analyses, raw reads were quality-, adapter-, and polyA-trimmed using Cutadapt ( 21 ) and unique molecular identifier and linker sequences were removed before the processed reads were aligned to the human genome (GRCh38) with Ensembl gene annotation (release 80) using STAR (version 2.7.6a) ( 22 ).…”
Section: Methodsmentioning
confidence: 99%